A randomized double‐blind clinical trial evaluating comparative plaque and gingival health associated with commercially available stannous fluoride‐containing dentifrices as compared to a sodium fluoride control dentifrice - Geisinger, Maria L.; Geurs, Nicolaas C.; Novy, Brian; Otomo‐Corgel, Joan; Cobb, Charles M.; Jacobsen, Peter L.; Takesh, Thair; Wilder‐Smith, Petra (Journal of periodontology (1970), 2023)
Background Gingivitis is a non‐specific inflammatory lesion in response to the accumulation of oral biofilm and is a necessary precursor to periodontitis. Enhanced oral hygiene practices, including utilization of a dentifrice that could significantly improve plaque accumulation and gingival inflammation, is desirable to prevent and treat gingivitis and potentially prevent progression to periodontitis. This clinical study aimed to investigate the effect of a new stannous fluoride‐containing dentifrice with 2.6% ethylenediamine tetra acetic acid (EDTA) as an anti‐tartar agent to reduce plaque index and gingival index over a 3‐month study period compared to other commercially‐available fluoride‐containing dentifrices. Methods This double‐blind, randomized controlled clinical study evaluated plaque, gingival inflammation, and sulcular bleeding in patients using one of five commercially available fluoride‐containing dentifrices The dentifrices tested contained: 0.454% stannous fluoride and 2.6% EDTA (D1), 0.24% sodium fluoride (C), and 0.454% stannous fluoride (D2‐D4). One hundred fifty subjects participated over a 3‐month period. Co‐primary endpoints were improvements in plaque index (PI) and modified gingival index (mGI) from baseline values. No professional cleaning was performed during the study period. Results All subjects in the study demonstrated statistically significant improvements in all measures of oral hygiene over the 3‐month study period. Subjects using dentifrice 1 (D1) showed statistically significantly greater reductions in PI, mGI, and modified sulcular bleeding index (mSBI) compared with all other commercially‐available dentifrices tested (p < 0.00001). Conclusions A new dentifrice with 0.454% stannous fluoride and 2.6% EDTA demonstrated significant improvements in clinical parameters associated with gingivitis compared to other sodium and stannous fluoride containing dentifrices.